The gender differences in the relationships between self-esteem and life satisfaction with social media addiction among university students - Yap, Jing Xuan; Che Amat, Muhammad Asyraf (Canadian Center of Science and Education, 2021)
Recent evidence indicates an elevated risk of social media addiction in university students. This research was designed to enhance the understanding of social media addiction among university students by investigating the relationships between self-esteem, life satisfaction, and social media addiction, with the possibility of gender differences in the relationships. 288 university students (103 males, 185 females) from the Faculty of Educational Studies at Universiti Putra Malaysia (UPM) done the Social Media Addiction, Rosenberg Self-Esteem (RSES), and Life Satisfaction Scales. Results showed that self-esteem and life satisfaction accounted for 64% of the total variance in social media addiction. Life satisfaction was a significant factor in increasing the possibility of social media addiction. On the contrary, there were no significant differences in life satisfaction and self-esteem, the latter exhibited no association with social media addiction. Furthermore, males were much more addicted to social media than females. An understanding on gender differences may be helpful for clinicians to expand suitable therapy by taking into account these findings, meanwhile, the statistically significant differences between the variables may contribute to predict student addiction levels in social media. The results of this study are obtained from Malaysian university students and possible generalisation to other populations should be verified by further studies.